Fifty Shades of Grey: giving colour to the poorly known Angolan Ashy reed frog (Hyperoliidae: Hyperolius cinereus), with the description of a new species - Conradie, Werner; Branch, William R.; Tolley, Krystal A. (Zootaxa, 2013)
Phylogenetic reconstruction using the mitochondrial 16S marker shows that geographically separated populations of the poorly known Hyperolius cinereus (Anura: Hyperoliidae) from Angola form two distinct clades. The description of H. cinereus was originally based on only a single preserved adult male. Fresh material of both sexes allowed a detailed redescription of the species, which is restricted mainly to the south-draining Cunene and Cubango river systems. Bioacoustic and morphological characters, in conjunction with colouration differences, allow the description of a cryptic sister species from Lagoa Carumbo in north-eastern Angola, occurring in the Luele and Lovuo river systems of the Congo drainage basin. Tadpoles, for H. cinereus and the new species, are described.